2016
DOI: 10.14719/pst.2016.3.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Acute consumption of Peppermint and Chamomile teas produce contrasting effects on cognition and mood in healthy young adults

Abstract: This study aimed to assess the acute effects of Peppermint and Chamomile herbal teas on cognitive performance and mood in healthy young adults. A single factor independent groups design was employed. One hundred and eighty undergraduate students volunteered to take part in the study for which they received course credit. Participants were randomly allocated to one of three treatments: Peppermint tea, Chamomile tea or hot water (Control). Mood scales were completed and participants then consumed their drink ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Chamomile is characterized as low -growing apple scent expressing its Greek name Chamos (ground) and melos (apple) [7]. It presents a pleasant taste with various medicinal effects including anti-inflammatory, anticancer (skin, breast, ovarian, or prostate), antioxidant, antiphlogisitis, treatment of wound, acute viral nasopharyngitis (known as common cold), infant colic disorder, haemorrhoids, mucositis, osteoporosis, vaginitis, improving cardiac health, managing diabetes, sleep, sedation, anxiety, seizure, eczema, digestive disorders, diminishing hyperglycaemiarelated oxidative stress, and others [1,8,9]. Numerical Taste predication (Table (1), Figure (2)) confirmed sour probability of the tested constituents ranged (o.537-1) for bitter, (0.546-0.989) for sweet, and (0.834-1) for sour character.…”
Section: Resultsmentioning
confidence: 99%
“…Chamomile is characterized as low -growing apple scent expressing its Greek name Chamos (ground) and melos (apple) [7]. It presents a pleasant taste with various medicinal effects including anti-inflammatory, anticancer (skin, breast, ovarian, or prostate), antioxidant, antiphlogisitis, treatment of wound, acute viral nasopharyngitis (known as common cold), infant colic disorder, haemorrhoids, mucositis, osteoporosis, vaginitis, improving cardiac health, managing diabetes, sleep, sedation, anxiety, seizure, eczema, digestive disorders, diminishing hyperglycaemiarelated oxidative stress, and others [1,8,9]. Numerical Taste predication (Table (1), Figure (2)) confirmed sour probability of the tested constituents ranged (o.537-1) for bitter, (0.546-0.989) for sweet, and (0.834-1) for sour character.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding peppermint essential oil, previous studies have confirmed its relaxing and sedative effects (Lisa Blackburn et al, 2017). In other words, this essential oil can decrease fatigue, anxiety, heart rate, respiratory rate, and blood pressure, increase the oxygenation of the lungs and brain, and improve sleep quality (Meamarbashi, 2014;Moss et al, 2016;Meamarbashi & Rajabi, 2013;Cruz et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…However, the results of several studies have indicated that aromatherapy with peppermint essential oil has positive effects on decreasing the heart rate, respiratory rate, blood pressure, fatigue, and anxiety. It also relaxes the bronchial muscles, and increases oxygenation in the lungs and brain (Meamarbashi, 2014;Moss et al, 2016;Meamarbashi & Rajabi, 2013;Cruz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of two single-blind studies, peppermint tea increased alertness and improved accuracy and speed of memory task performance 20 min after consumption, in comparison to a hot water control, in 180 young adults [ 161 ]. In the second, the only study to date involving physical performance, pure peppermint essential oil dripped onto the tongue improved auditory and visual reaction times 5 min and 1 h after administration and improved lung function and physical performance (grip force, standing vertical and long jump) in comparison to a water control in 30 participants [ 162 ].…”
Section: Terpenesmentioning
confidence: 99%